Dinamika Pesantren Dan Madrasah Dalam Perjalanan Sejarah Pendidikan Islam Di Kabupaten Ogan Komering Ulu - Faozan; Azwar Aripin (Genta Bangsa : Jurnal Ilmu Pendidikan, 2026)
Pesantren and madrasah are Islamic educational institutions that have played an important role in shaping the socio-religious development of Indonesian society. This study aims to analyze the dynamics of pesantren and madrasah in the historical development of Islamic education in Ogan Komering Ulu (OKU Regency). This research employs a qualitative approach using historical methods through literature studies, document analysis, and examination of historical sources related to local Islamic education development. The findings indicate that pesantren have functioned as centers for religious knowledge transmission, character building, and the regeneration of Islamic scholars, while madrasah have represented the modernization of Islamic education through the integration of religious and general sciences. The development of these institutions demonstrates their ability to adapt to social changes, national education policies, and globalization challenges while maintaining Islamic identity. Pesantren and madrasah in OKU have also contributed as agents of social transformation through community empowerment, preservation of Islamic culture, and the development of local leaders. This study confirms that pesantren and madrasah remain essential foundations for the sustainability of Islamic education at the regional level.